Transitioning to more sustainable livestock systems through agricultural breakthroughs - International Livestock Research Institute (International Livestock Research Institute, 2023)
This film provides guidance on the transition to more sustainable livestock production systems for both high-income countries and low-middle income countries and the different types of production systems found there. Though technologies such as methane inhibitors may have a role in systems where feed is regulated, in pasture and grazing led systems the only effective approach to reduce methane emissions is through supporting an increase in climate-smart livestock practices.